STUDI KELAYAKAN DAN STRATEGI PENGEMBANGAN BUDIDAYA UDANG VANAME (Litopenaeus vannamei) PADA TAMBAK PLASTIK DI KABUPATEN KAUR BENGKULU (Studi Kasus pada PT XYZ) - Bambang Nardiyanto; Muhammad Irfan Affandi; Ktut Murniati (Lampung University, 2019)
PT XYZ plans to expand its business. For this reason, the purpose of this research is to analyze the feasibility of the planned expansion of vannamei shrimp farming in PT XYZ and formulate a strategy for developing vannamei shrimp cultivation at PT XYZ. This research was conducted at PT XYZ, located in Padang Hangat Village, Central Kaur District, Kaur Regency, Bengkulu Province. The analytical methods used were net present value (NPV), internal rate of return (IRR), benefit-cost ratio, payback period and SWOT analysis tools implemented by examining internal and external factors. The conclusion in this study was that the planning of land expansion of vannamei shrimp farming conducted by PT XYZ was feasible, because it would provide a profit value of Rp. 134,512,309,054.00 with an IRR value of 12.78 percent and a payback period value of 1.04 year or for 1 year 14 days. The strategy for developing vannamei shrimp farming was to carry out production management planning to meet demand on time, amount, and quality; carry out production management planning by implementing CBIB; increase production volume by utilizing and optimizing existing land; cooperate with the government to find solution of various obstacles faced; and collaborate with academics to conduct product research and development. Key words: Feasibility study, strategy of development, vannamei shrimp